THE PROBLEM OF MANNED AIRCRAFT CONVERSION INTO UNMANNED AERIAL VEHICLES - Belan, Vladimir; Gnashuk, Andreii; Yun, Gennadiy (Proceedings of National Aviation University (archive), 2018)
Purpose: an attempt to systematize and outline the theoretical and practical methods for solving the problems that arise when creating a UAV based on mass-produced light and ultra-light aircraft. Methods: it is assumed that the aircraft as a multidimensional dynamic system can be described by a matrix of transfer functions, whose elements can be obtained from estimates of the spectral characteristics, which are calculated from the records of the input and output signals. A multi-stage process for achieving the goal is proposed. A multi-stage process for achieving the goal is proposed. At the first stage, a mathematical model of the aircraft is constructed using the methods of identification and estimation of the parameters of dynamic systems. At the first stage, a mathematical model of the aircraft is constructed using the methods of identification and estimation of the parameters of dynamic systems. Results: the algorithm for the conversion of light and ultra-light manned aircraft into unmanned aerial vehicles based on the statistical method of spectral analysis is formulated. Next, it is planned to adapt the developed control algorithm and carry out the necessary studies on a manned prototype aircraft. The implementation of the flight program on a manned prototype aircraft with readout of control parameters in the autopilot mode will make it possible to update the mathematical model and the control algorithm for an unmanned aerial vehicle. Discussion: questions of the evaluation of the effectiveness and practical value of the proposed control algorithm required a large amount of additional numerical experiments on the example of a specific unmanned aerial vehicle for agricultural purposes. Therefore, the conclusions on the methodological and practical value of the proposed approach to the design of agricultural unmanned aerial vehicles can be made only after performing the full volume of flight tests on the experimental sample.